2020
DOI: 10.37558/gec.v18i1.762
|View full text |Cite
|
Sign up to set email alerts
|

Marco metodológico para la conservación preventiva de murallas históricas emplazadas en contextos urbanos. Normalización de datos espaciales relativos a la muralla medieval de Sevilla (España): el caso del sector de la Macarena[1]

Abstract: La gestión de inmuebles históricos encuentra problemáticas específicas en el caso del patrimonio fortificado que se localiza en contextos urbanos: demoliciones, afecciones arqueológicas, deterioro, etc. Dichas cuestiones se ejemplifican en el caso de la muralla medieval de Sevilla, construida prevalentemente en tierra mediante la técnica del tapial. Estas entidades, de gran extensión y elevada complejidad, resultan idóneas para el empleo de sistemas de información geográfica (SIG). La gestión cartográfica digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…It is made of rammed earth, whose density was assumed to be 20 kN/m 3 according to physical tests on cored samples from several sector of the Seville city walls [11,35,36], which are in fact consistent with similar results in the literature [10,37,38]. [39,40]. Subsequently, some trenches were made near the wall towers to investigate the foundation level of the wall together with the type of soil, temporarily removing the backfill on the stem.…”
Section: Cases Selectionmentioning
confidence: 65%
See 2 more Smart Citations
“…It is made of rammed earth, whose density was assumed to be 20 kN/m 3 according to physical tests on cored samples from several sector of the Seville city walls [11,35,36], which are in fact consistent with similar results in the literature [10,37,38]. [39,40]. Subsequently, some trenches were made near the wall towers to investigate the foundation level of the wall together with the type of soil, temporarily removing the backfill on the stem.…”
Section: Cases Selectionmentioning
confidence: 65%
“…Although the configuration on both sides of the Macarena Wall is similar along its entire length, the third stretch starting from Saint Hermenegildo Church has been selected to carry out this study. According to the archaeological intervention directed by Florentino Pozo in 2008 [39,40], the rampart is 1.90 m thick, and its foundation is located at a level of 6.52 m. This research campaign has revealed that there is a slight difference in the topography of Macarena Street, with a level of 9.80 and 9.52 m at the north and south sides, respectively. There is also a slight difference in the top level of the wall at the border with the towers, ranging from 15.25 to 15.06 m. In both cases an average value has been considered.…”
Section: Cases Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartographic Management (DCM) is positioned as a validated protocol for the multidisciplinary study of historic buildings, from different scales and degrees of complexity. This protocol is based on the use of simplified models that allow the definition of the architectural scale, facilitating the subsequent use of threedimensional tools (Canivell et al 2020) This work is part of the tasks promoted by the "Specific collaboration agreement between the University of Seville and the Urban Planning Management of the City Council of Seville, for the development of strategies aimed at the restoration and subsequent preventive conservation of the medieval wall of Seville". This agreement, initiated in 2019, aims to design a comprehensive preventive conservation plan for the preserved sectors of the medieval wall of Seville (Canivell et al 2019).…”
Section: Digitalmentioning
confidence: 99%
“…The application of these levels provides a clear flexibility in the definition of the elements of the wall, from the urban scale to the architectural detail. This hierarchical system of levels is set out in detail in Canivell et al 2020, and it is briefly explained bellow.…”
Section: Starting Pointmentioning
confidence: 99%